The Emerging Role of Ferroptosis in Cardiovascular Diseases - Min Hong; Jiabing Rong; Xinran Tao; Yinchuan Xu (Frontiers Media S.A., 2022)
Ferroptosis is one type of programmed cell death discovered in recent years, which is characterized by iron-dependent lipid peroxidation and participating in iron, lipid and antioxidant metabolism. Ferroptosis is different from the traditional cell death types such as apoptosis, necroptosis and autophagy in morphology, biochemistry and genetics. Cardiovascular diseases are considered as an important cause of death from non-communicable diseases in the global population and poses a serious threat to human health. Apoptosis has long been thought to be the major type of cardiomyocyte death, but now ferroptosis has been shown to play a major role in cardiovascular diseases as well. This review will discuss related issues such as the mechanisms of ferroptosis and its effects on the occurrence and development of cardiovascular diseases, aiming to provide a novel target for the prevention and treatment of cardiovascular diseases.